Promoting reading skills in CLIL - Garipova, Nailya; Nicolás Román, Susana (Pulso. Revista de educación, 2016)
Content and Language Integrated Learning (CLIL) has been largely implemented in our educational institutions through different approaches. CLIL can encompass a wide variety of teaching resources but this new framework should constitute an innovative perspective to overcome the restraints of traditional school curricula in the teaching of foreign languages. Promoting reading skills comprehension is also considered essential in the CLIL approach (Wolff, 2005). However, despite its importance, few studies have focused their attention on the reading skills of CLIL in Spain (Pérez Cañado, 2012). The starting point of this study remarks the concept of reading as a complex process which involves different skills and strategies, also reinforced by the Common European Framework of Reference for Languages as a key element in the learning process. The first part of this article presents a general framework of CLIL as a methodological approach followed by an overview of the reading skill and its main characteristics and potentiality in the classroom. The second part of the article provides guidelines regarding the strategies and types of reading activities that may help students become proficient readers.